Original paperIn vivo evaluation: the effects of a cream containing Acacia bark extract on skin melanin and erythema content - Ali, Atif; Akhtar, Naveed; Khan, Muhammad Shoaib (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction: Phenolic compounds have inhibitory effects on tyrosinase and inflammatory activities which lead to reduction in the melanin and erythema content. This is important for hyperpigmentation, dermatitis and other oxidative stress diseases. Aim : Investigation of the effects of a cream containing phenolic-rich extract of Acacia bark on the human skin melanin and erythema content. Material and methods: Eleven healthy male volunteers were analyzed and treated with active cream versus base for a period of three months by non-invasive bioengineering techniques. Results : No serious adverse effects were observed after patch testing. Base showed insignificant results and active cream showed a significant decrease in skin melanin and erythema content after statistically applied ANOVA. Conclusions: Our results show that the Acacia bark extract represents a valuable source of phenolic compounds produced naturally. Treatments of human skin with active cream containing phenolic-rich Acacia bark extract significantly reduce skin melanin and erythema in vivo and could be used for topical treatment of hyperpigmentation and dermatitis.